КОНЦЕПЦІЯ ПОБУДОВИ ГІБРИДНОЇ СИСТЕМИ КЕРУВАННЯ МІКРОГІДРОЕЛЕКТРОСТАНЦІЄЮ - Зайченко, О.А.; Маруня, Ю.В.; Рижков, О.М.; Гаврилюк, С.І.; Хомицький, О.І.; Харченко, О.О. (Інститут електродинаміки НАН України, Київ, 2024)
Methods of increasing the energy efficiency of micro-hydroelectric power plants are considered in the work. A new hybrid concept of building a control system is proposed, which combines classical control laws and fuzzy logic. This makes it possible to improve the quality of the regulation of the parameters of the generated electricity regardless of changes in network operation modes and external conditions. It is shown that the use of hybrid filters will allow to increase the electromagnetic compatibility and, as a result, the energy efficiency of the system as a whole. Referensces 12, figures 3.